Implementation of care for the use of the extracorporeal oxygenation membrane in the COVID-19 pandemic - Ligia Neres Matos; Julia Gonçalves Escossia Campos; Liana Amorim Corrêa Trotte; Marluci Andrade Conceição Stipp (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objective: To report the experience of a quaternary care center on the implementation of a care program for patients with severe hypoxemic respiratory failure due to SARS-CoV-2 requiring an extracorporeal oxygenation membrane. Method: This is an experience report with a descriptive approach, analyzing the use of the extracorporeal oxygenation membrane in a quaternary care center in the city of Rio de Janeiro. Results: The planning for the use of the extracorporeal oxygenation membrane included training with the professionals and use of the components related to the adaptation of the protocol, equipment, facilities, quality and safety. Final Considerations: Planning, resource allocation and regular training of the team to offer complex interventions, in line with recommendations for good practices in the care for patients with pulmonary complications related to the new coronavirus were essential for the development of the action plan for the use of extracorporeal oxygenation membrane in this pandemic period.